Recording Solo: Managing Long-Distance Data Collection within Audio Diary Research with Healthcare Professionals - Moretti, Veronica (Qualitative Sociology Review, 2025)
This paper explores the methodological and reflexive implications of using audio diaries in remote qualitative research with healthcare professionals. Drawing on a three-month study involving 18 participants who submitted audio recordings weekly, complemented by follow-up interviews, the article examines how this method enables the collection of rich, emotionally nuanced, and temporally proximate narratives. The audio diary format proved particularly effective for engaging professionals under high emotional and organizational pressure, offering a flexible and participant-led space for reflection. The study also sheds light on the challenges of sustaining participation over time, the importance of ethical responsiveness, and the role of the researcher in supporting engagement at a distance. Ultimately, the paper proposes the concept of long-distance reflexivity to describe how both participants and researchers negotiate meaning, presence, and vulnerability in fully remote research settings.